L’iconographie et le symbolisme du palmier dattier dans l’Antiquité (Proche-Orient, Égypte, Méditerranée orientale) - Fanny Michel-Dansac; Annie Caubet (Revue d'ethnoécologie)
The date palm (Phoenix dactylifera) plays an important role in the ideologies of past civilisations. This paper addresses the origin and development of the motif in the vast zones of agricultural production (oases of Egypt and Mesopotamia) from the late 4th millennium BC, as well as its diffusion towards the Eastern Mediterranean world where the date palm, although deprived of real economic value, still retains or acquires new and multiple symbolic significations. The recurrence of certain symbolic themes allows us to note how the plant is perceived in different cultural and religious contexts: associated with water and women, the palm tree becomes a symbol for the ritual space.